2015
DOI: 10.7287/peerj.preprints.1280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is HTTP/2 more energy efficient than HTTP/1.1 for mobile users?

Abstract: Recent technological advancements have enabled mobile devices to provide mobile users with substantial capability and accessibility. Energy is evidently one of the most critical resources for such devices; in spite of the substantial gain in popularity of mobile devices, such as smartphones, their utility is severely constrained by battery life. Mobile users are very interested in accessing the Internet while it is one of the most expensive operations in terms of energy and cost. HTTP/2 has been proposed and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…HTTP/2 optimizations have been shown to save energy for the mobile client side devices [56]. In our previous study [14], we also found client-side HTTP/2 to be more energy efficient than HTTP/1.1 with or without Transport Layer Security (TLS) applied. However, does these optimizations and reduction in PLT helps HTTP/2 speaking servers to be more energy efficient than HTTP/1.1?…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…HTTP/2 optimizations have been shown to save energy for the mobile client side devices [56]. In our previous study [14], we also found client-side HTTP/2 to be more energy efficient than HTTP/1.1 with or without Transport Layer Security (TLS) applied. However, does these optimizations and reduction in PLT helps HTTP/2 speaking servers to be more energy efficient than HTTP/1.1?…”
Section: Introductionmentioning
confidence: 86%
“…Following the work done previously [14], we once again used FGallery [17], a static photo gallery generator and deployed it onto the H2O and the Jetty server. The Fgallery resources deployed consists of the home HTML page, CSS, JS, JSON and Image files.…”
Section: Workloadmentioning
confidence: 99%
See 3 more Smart Citations